Characterisation of Achilles tendon pain in recreational runners using multidimensional pain scales. Issue 3 (March 2020) - Mkumbuzi, Nonhlanhla S.; September, Alison V.; Posthumus, Michael; Oulo, Brenda; Mafu, Trevor S.; Collins, Malcolm
Abstract: Objectives: The main assessment tool for Achilles tendinopathy (AT) is the VISA-A. However, the VISA-A only assesses the physical impairments that result from tendon pain. This study sought to describe and assess tendon pain using other multidimensional pain scales; the short forms of the McGill pain questionnaire (sf-MPQ) and the Brief Pain Inventory (sf-BPI). Design: Cross sectional observational study. Methods: 124 recreational runners with clinically confirmed mid-portion Achilles tendinopathy for at least 3 months were recruited from Cape Town, South Africa. They described and rated their tendinopathy symptoms by completing the VISA-A, sf-BPI and sf-MPQ questionnaires. Results: Tendon pain was largely described as a sensory type of pain with minimal affective elements. Sixty percent described their pain as aching. Significant proportions described it as tender (52.9%), throbbing (33.9%), hot burning (24.8%) and 33.8% ranked it as discomfiting or worse on the pain intensity score of the sf-MPQ. Tendon pain interfered with mood in 50.8% of the participants as well as with walking ability (72.5%), sleep (34.8%) and enjoyment of life (54.2%). Conclusions: Tendon pain was described using a variety of adjectives which may suggest that AT has clinical subtypes. Tendon pain interferes with more than just physical function. Therefore, the recommendation is to conduct further studies using various pain questionnaires to elicit more details and better understand the nature of Achilles tendon pain.